Reflections on the Impact of Extreme Weather on New Power Systems and Countermeasures - Chen CAO; Zengping WANG (南方能源建设)
[Objective] In recent years, climate warming and other factors have led to a rise in extreme weather events globally. Simultaneously, under the "carbon peak - carbon neutral" goal, the integration of fluctuating renewable energy including wind and solar energy, extensive use of power electronics and long-distance ultra-high-voltage transmission have reshaped traditional power grids. These changes have increased the exposure of primary equipment to harsh environments, intensifying the vulnerability of power systems to extreme weather impacts. [Method] This paper reviewed the impact of recent extreme weather events, such as typhoons, heavy rainfall and ice storms, on power system equipment and operations. It explored systemic risk performance in depth in new power systems through case studies and proposed strategies for refined modeling, systemic risk assessment and cross-disciplinary collaboration across disaster scenarios. [Result] The research shows that extreme weather significantly increases the risks of equipment failures and system instability, with high renewable energy penetration amplifying the impact of failure propagation. [Conclusion] The safe operation of power systems under the dual pressure of in-depth construction of new power systems and intensified impact of extreme weather relies on improvement of equipment risk modeling, systemic risk control and cross- disciplinary collaboration mechanisms. Therefore, future research should focus on building multi-dimensional joint risk assessment of power systems. In addition, the paper points out the significance of strengthening in-depth integration of power systems and meteorological systems for enhancing risk prediction and dynamic response capabilities of the system, thus providing scientific basis and technical support for improving the system resilience.